Social support and well-being of the children of prisoners - Norizan, Abdul Ghani; Che Siti Noradliza, Mahmud (2012)
Growing up with incarceration issues can be a devastating experience for children. Incarceration brings long term effects to family members by increasing more serious emotional, behavioral and psychological suffering among children; impeding children to have a better picture of well-being. According to Button and Phipps (2008), social support especially from family members plays an important role in helping children to cope with this devastating experience. Using six selected indicators for child well-being based on the suggestion from Land and colleagues (2001), we assessed the effects of social support on children’s well-being with incarceration issues in the Malaysian state of Kelantan. There were three indicators that correlated with child well-being, selected based on the current literature related to the social support; help in study, family concern and close with guardian. The relationship between child’s well-being and social support affects were examined in 75 children aged 8 to 17 years with family incarceration issues in Kelantan. The results suggested that when there was more social support (more time with child and help in study) from the care taker, children would have a higher level of well-being. Results of this study also revealed that children who perceived higher attention from family in their studies and life had a higher level of competence and self-esteem.